Pengaruh Model Pembelajaran Kooperatif Tipe Write Around terhadap Hasil Belajar Bahasa Inggris Siswa Kelas IV SD GMIM 92 Bailang - Non Norma Monigir; Regina K. Sarudi; Nofry V. Wongkar (Departement of Mathematics Education, 2024)
This study aims to determine the effect of the Write Around cooperative learning model on the English learning outcomes of fourth-grade students of SD GMIM 92 Bailang with public space material. The method used in this study is a quantitative method with data analysis using the SPSS program. The subjects of the study consisted of 22 students who were given treatment using the Write Around cooperative learning model. This study used an experimental design with pretest and posttest to measure changes in student learning outcomes. The results of the analysis showed that there was a significant effect of using the Write Around cooperative learning model on improving students' English learning outcomes, especially in understanding public space material. This is evidenced by the results of the t-test (paired sample t-test) which showed a significant difference between the pretest and posttest scores. Based on these findings, the Write Around cooperative learning model can be used as an alternative to improve the English learning outcomes of fourth-grade students of SD GMIM 92 Bailang.